INCREASED KNOWLEDGE ABOUT THE IMPACT OF GADGETS, DRUGS AND PROMISCUITY ON ADOLESCENTS IN MAN 1 ACEH BESAR - Lensoni; Erna; Safira, Meylia; Hidaya; Safira, Safra; Wahyu, Reski; Amalia, Rizka; Rahmadani, Sukri; Lukman; Julianti (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
The negative influence of gadgets, promiscuity, and drugs on students can be prevented as well as maintaining the reproductive health of women through the dissemination of reproductive health advice. It is hoped that after being given this research, students can understand the impact of gadget gadgets, the dangers of drugs, and promiscuity as well as tips on maintaining reproductive health in women. The aim of this study was to determine the effect of providing counselling on knowledge about the impact of gadget gadgets, the dangers of drugs, and promiscuity on students at MAN 1 Aceh Besar. The research design used is a pre-experimental design with one group pretest-posttest design. The population is 20 students of MAN 1 Aceh Besar of XI grade. The sampling technique used is total sampling. The data obtained were analyzed using a paired simple t-test statistical test with a degree of meaningfulness of 95% (0.05). The results of the research data collection were mostly 4 (20.0%) moderate category respondents' knowledge, most of the respondents' knowledge was 18 (90.0%) on the high category. The results of the bivariate analysis show that p-value = 0.00 means p value < 0.05. In other words, there is an influence between the provision of research on knowledge in MAN 1 Aceh Besar students about the impact of gadgets, the dangers of drugs and promiscuity and reproductive health on women.